Covid-19 Pandemic and labour relations: Some hypotheses - Vincenzo Ferrari (Cuadernos Electrónicos de Filosofía del Derecho, 2023)
In this essay, the author frames some initial hypotheses about the effects that the Covid-19 Pandemic may have produced in the field of labour relations, with a special focus on remote working. He examines some data referred to the European context in general, as well as those of some countries (in particular Italy, France, Germany, Spain and the United Kingdom, with an extension to the United States), and observes that such data, albeit fragmentary and still incomplete, reveal that apart from some oscillations due to the contingencies of the pandemic, remote working seems set to become stable in the years to come. This would produce consequences of considerable scope, in that it would oblige some fundamental aspects of both labour relations and workers’ private lives to be restructured.